First-year mortality in incident dialysis patients: results of the Peridialysis study - Heaf James; Heiro Maija; Petersons Aivars; Vernere Baiba; Povlsen Johan V.; Sørensen Anette Bagger; Clyne Naomi; Bumblyte Inga; Zilinskiene Alanta; Randers Else; Løkkegaard Niels; Rosenberg Mai; et al. (BMC, 2022)
Background:
Controversy surrounds which factors are important for predicting early mortality after dialysis initiation (DI). We investigated associations of predialysis course and circumstances affecting planning and execution of DI with mortality following DI.
Methods:
Among 1580 patients participating in the Peridialysis study, a study of causes and timing of DI, we registered features of predialysis course, clinical and biochemical data at DI, incidence of unplanned suboptimal DI, contraindications to peritoneal dialysis (PD) or hemodialysis (HD), and modality preference, actual choice, and cause of modality choice. Patients were followed for 12 months or until transplantation. A flexible parametric model was used to identify independent factors associated with all-cause mortality.
Results:
First-year mortality was 19.33%. Independent factors predicting death were high age, comorbidity, clinical contraindications to PD or HD, suboptimal DI, high eGFR, low serum albumin, hyperphosphatemia, high C-reactive protein, signs of overhydration and cerebral symptoms at DI. Among 1061 (67.2%) patients who could select dialysis modality based on personal choice, 654 (61.6%) chose PD, 368 (34.7%) center HD and 39 (3.7%) home HD. The 12-months survival did not differ significantly between patients receiving PD and in-center HD.
Conclusions:
First-year mortality in incident dialysis patients was in addition to high age and comorbidity, associated with clinical contraindications to PD or HD, clinical symptoms, hyperphosphatemia, inflammation, and suboptimal DI. In patients with a"free"choice of dialysis modality based on their personal preferences, PD and in-center HD led to broadly similar short-term outcomes.